ANALISIS MEMBERSHIP PROGRAM ("SHELL CLUBSMART") DALAM UPAYA MENCIPTAKAN BRAND LOYALTY CONSUMER DI SPBU SHELL AREA DKI JAKARTA - Anita Kurniati Abadiyah, (2021)
This quantitative research aims to understand and analyze the effect of Membership on Brand Loyalty at DKI Jakarta Shell Area Gas Station, to find out and analyze the effect of Membership on Customer Satisfaction at DKI Jakarta Area Shell Gas Station, to determine and analyze the effect of Customer Brand Engagement on Brand Loyalty at Shell Gas Station DKI Jakarta Area, to find out and analyze the influence of Customer Brand Engagement on Customer Satisfaction at DKI Jakarta Shell Area Gas Station. To find out and analyze the influence of Customer Satisfaction on Brand Loyalty at DKI Jakarta Shell Area Gas Station. The research sample is Shell SPBU consumers with a total of 100 respondents or who frequently conduct transactions in DKI Jakarta Shell Area SPBU using membership ("Shell Smart Club") and accessing it from the Shell SPBU website. While the data analysis uses PLS (Partial Least Square). The results of this study indicate that (1) Membership has a significant effect on Customer Statisfaction with a tcount of 2.298> t table 1.985 and a P value of 0.022 <0.05. (2) Customer Brand Engagement has a significant effect on Customer Satisfaction with a tcount of 11.879> t table 1.985 and a P Value of 0.000 <0.05. (3) Membership has no significant effect on Brand Loyalty with a tcount of 1.544 <ttable 1.985 and a P Value of 0.123> 0.05. (4) Customer Brand Engagement has a significant effect on Brand Loyalty with a value of 5.857> t table 1.985 and a P value of 0.000 <0.05. (5) Customer Satisfaction has a significant effect on Brand Loyalty with a tcount of 2.812> t table 1.985 and a P Value of 0.005 <0.05. The positive influence between Customer Brand Engagement on Brand Loyalty is 0.733, Customer Brand Engagement on Customer Satisfaction is 0.766, Customer Satisfaction on Brand Loyalty is 0.289 and Membership against Customer Satisfaction is 0.173. but there is also a negative that is the Membership of Brand Loyalty of -0.151.